Isolation, identification and pathogenic mechanism analysis of a Bacillus strain from Macrobrachium nipponense with red hepatopancreas. (3rd November 2021) - Nie, Qing; Xia, Jiaoyang; Zhao, Weihong; Yan, Qingqing; Geng, Bin; Qiao, Guo; Lv, Fu; Lv, Linlan; Jiang, Fengjuan; Liu, Longyu
Abstract: The oriental river prawn, Macrobrachium nipponens e, is an economically and nutritionally important freshwater crustacean in China. However, in recent years, some diseases have emerged in M . nipponense . In the present study, a pathogenic bacterium from M . nipponense with a red hepatopancreas was isolated. Then, through phenotypic analysis, biochemical analysis and genotypic identification, the MN strain was identified as a member of the Bacillus cereus group. The pathogenic mechanism analysis showed that the MN strain had virulence genes, including nheA, cytK and bceT gene, and could secrete urease and haemolysin. Furthermore, the drug sensitivity test suggested Cefazolin, amikacin, gentamicin and chloramphenicol could significantly inhibit the growth of the MN strain. All these results provide a theoretical basis for clinical medication to prevent or treat disease caused by MN strain in M . nipponense .